Kerentanan dan Kerusakan Beras terhadap Serangan Hama Pascapanen Sitophilus zeamais L. (Coleoptera: Curculionidae) - Hendrival, Hendrival; Mayasari, Eva (Jurnal AGRO, 2017)
Damage on rice during storage including damage on quantity and quality is caused by Sitophilus zeamais. The study aim was to evaluate the susceptibility and damage of rice from various rice varieties to the attacks of S. zeamais. Types of rice used in the research were varieties of IR64, IR65, IR66, Ciherang, Mekongga, Rojolele, and Sintanur. The method was with no-choice assay with observed variables were F1 progeny number, the median of development time and rice damage. The results showed that the rice type had different levels on susceptibility to S. zeamais. Rice from IR65, Mekongga, Rojolele, and Sintanur varieties were classified as moderate to susceptible varieties, while IR64 and IR66 were classified as moderate varieties and Ciherang was classified as susceptible variety. A high rice damage occured in the type of rice classified of susceptible to S. zeamais. There was a significant negative correlation between susceptibility index of rice with dimensions of rice width (r = -0.75*, P <0.05) and median of development time of S. zeamais (r = -0.78*, P <0.05) and positive correlation with number of F1 S. zeamais (r = 0.86**, P <0.01) and the percentage of rice powder (r = 0.71**, P <0.01). Rice that is easily attacked by postharvest pest insects should not be stored for long period of time.